Harmful Effects of COVID-19 on Major Human Body Organs: A Review - Md. Rayhan Chowdhury; Md. Atik Mas-ud; Md Roushan Ali; Mst Fatamatuzzohora; Ajmeri Sultana Shimu; Md. Anamul Haq; Md. Ashikul Islam; Md. Firose Hossain; Md. Hosenuzzaman; Md. Mominul Islam; Md. Faruk Hasan; Mohammad Nurul Matin (Journal of Pure and Applied Microbiology, 2021)
The world experienced the outbreak of a new pandemic disease in 2019, known as coronavirus (CoV) disease 2019 (COVID-19), which is caused by the novel severe acute respiratory syndrome-CoV-2 (SARS-CoV-2). The respiratory system is the organ system most commonly affected by COVID-19; however, several other organ systems have been reported to be affected. The SARS-CoV-2 RNA found in infected stub samples can cause lung contagion by binding to the angiotensin-converting enzyme-2 (ACE-2) receptor of the alveolar epithelial cells. The gut microbiota (GM) promote immunity, indicating that the alignment of the microbiota and corresponding metabolic processes in COVID-19 can help to identify novel biomarkers and new therapeutic targets for this disease. The cause of kidney damage in COVID-19 patients is possibly multifactorial, involving a complex mechanism that involves complement dysregulation and thrombotic microangiopathy, as well as the occurrence of a “cytokine storm” syndrome, which are immune responses that are abandoned and dysfunctional with unfavorable prognosis in severe COVID-19 cases. Furthermore, COVID-19 involves a continuous proliferation and activation of macrophages and lymphocytes. SARS-CoV-2 can also bind to the ACE-2 receptor expressed in the cerebral capillary endothelial cells that can invade the blood-brain wall, to penetrate the brain parenchyma. However, in the ongoing pandemic, there has been a surge in studies on a wide range of topics, including causes of respiratory failure, asymptomatic patients, intensive care patients, and survivors. This review briefly describes the damaging effects of COVID-19 on vital human organs and the inhibitory function of the ACE-2 receptor on the GM, which causes gut dysbiosis, and thus, this review discusses topics that have an opportunity for further investigation.